Analisis Produktivitas dan Pendapatan Usahatani Padi Sawah di Kecamatan Landawe Kabupaten Konawe Utara - Ratendra, Made Dwi; Yunus, Lukman; Alwi, La Ode (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The rice cultivation in the Landawe District, North Konawe Regency. The determination of this area is based on the consideration that in Landawe Subdistrict there are rice paddy farming. The research group is farmers in Landawe Subdistrict with a sample of 59 farmers, the sampling is done by simple random sampling (Random sampling). Based on this study, the results of several factors that have a significant effect on productivity, including urea and pesticides at the level of 10% and for seeds, NPK fertilizer and labor do not affect at the level of 10%. Based on income, the average income received by farmers is Rp. 11,081,122.8 / Ha.